Potential antifilarial activity of the fruit, leaf and stem extracts of Melia azedarach Linn. on cattle filarial parasite Setaria cervi in vitro - Ahmed, Qamar Uddin; Zaidi, SMKR; Kaleem, Mohammed; Khan, N. U.; Singhal, K. C. (Springer, Springer Korea Limited, Seoul, Korea (Rep.)., 2006)
The effect of aqueous and alcoholic extracts of the fruit, leaf and stem of Melia azedarach Linn.(Meliaceae) on the spontaneous movements of both the whole worm and the nerve-muscle(n.m.) preparation of Setaria (S.) cervi and on the survival of microfilariae in vitro was studied.Alcoholic extracts of fruit, leaf and stem caused inhibition of the spontaneous movements of thewhole worm and the n.m. preparation of S. cervi, while only aqueous extract of fruit causedinhibition of the spontaneous movements of the whole worm and the n.m. preparation of S.cervi. The initial stimulatory effect was not observed by the aqueous and alcoholic extracts offruit on n.m. preparation. The concentrations required to inhibit the movements of the wholeworm and n.m. preparation for alcoholic extracts of fruit, leaf and stem were 250, 40 µg/ml;280, 40 µg/ml and 270, 25 µg/ml respectively, whereas an aqueous extract of fruit causedinhibition of whole worm and n.m. preparation at 200 µg/ml and 40 µg/ml respectively.Alcoholic extracts of the fruit, leaf and stem and aqueous extract of the fruit of M. azedarachcaused concentration related inhibition on the survival of microfilariae (m.f.) of S. cervi. TheLC50 and LC90 as observed after 6 h were found to be 5, 15, 10, 20 ng/ml and 10, 25, 20 and 35ng/ml, respectively. This work was conducted in view of the exploration of potentialantifilarial herbal drug.